Analysis Of The Implementation Of Financial Management Of Regional Public Service Agency (BLUD) On The Performance Of Public Hospital Employees dr Djasamen Saragih - Kristianto Kristianto; Desmi Triyanti Purba; Hazelinling Hazelinling; Marintan Saragih; Yulita Santa Nova Girsang (Jurnal Ilmiah Accusi, 2024)
This study aims to analyze the implementation of financial management of the Regional Public Service Agency (BLUD) on the performance of employees at the Regional General Hospital (RSUD) dr. Djasamen Saragih. The research method used is descriptive analysis with a qualitative approach, using primary data obtained through interviews and field observations, as well as secondary data in the form of financial statements and related organizational documents. The results of the study show that BLUD financial management provides flexibility in planning and using the budget, which has a positive impact on the operational efficiency of the hospital. The implementation of the annual Business Plan and Budget (RBA), supervision by the supervisory board, and a reporting system in accordance with Financial Accounting Standards (SAK) support the improvement of employee performance. However, challenges such as maintaining a balance between public services and revenue, as well as the need to improve human resource competence, are still a concern. The study suggests regular training for employees and the development of innovative services to improve the efficiency and overall performance of the organization